Design of Buoyancy Adjusting Device based on the Gear-ball Screw Transmission - Sun Weizhi; Tan Hua (Jixie chuandong)
Based on the structure of gear- ball screw and piston,a buoyancy adjustment device is designed and driven by miniature dc- motor. Its structure and working principle are analyzed,and the relevant formulas of the mechanics are presented. The driving force is generated by miniature dc- motor and the ball nut linear motion is driven by the gear- ball screw transmission system. Because the ball nut and piston are connected by the piston cover,and then the hydraulic oil can be absorbed and injected by piston from hydraulic cylinder to oil bladder. The device is characterized with compact structure,easy control,precise movement and adjustment and etc. It can be combined with ocean sensors in a specific scope in order to realize the real- time collection of profiling ocean data.